Makings of a residential psychiatric program in hospitals in Lima - Jerí, Raúl (1965)
After briefly reviewing the requirements that hospitals must have programs to organize psychiatric residencies , the current state of psychiatric units Lima described the light of a survey taking into account the data of the Statistics Departments of the various nosocomios , responses to a questionnaire answered the caring staff from each service, and direct observations made ​​by the author . Given the deficiencies , training plan , to be carried out over a period of three to five years , in order to give sufficient knowledge and experience, according to current trends , for adequate preparation of psychiatrists proposed to enable the candidate to be able to pass a capacity of two stages: basic science and clinical psychiatry. Once passed exams to graduate be conferred the title of Specialist in Psychiatry .